Carbon stocks of fast growing tree species and baselines after forest fire in east Kalimantan, Indonesia - Diana, R.; Hadriyanto, D.; Hiratsuka, M.; Toma, T.; Morikawa, Y. (Forestry Research Institute, 2002)
In terms of sink activities in the Clean Development Mechanism (CDM) there is little information about carbon accumulation. This paper deals with case studies in natural young secondary forests and man made forests in East Kalimantan, Indonesia. East Kalimantan has high possibility of CDM activity, because of degraded lands extend widely in 1998. The annual carbon accumulation of pioneer secondary forest in Bukit Soeharto Educational Forest (BSEF) ranged from 1.3 to 2.9 t C/ha/yr in 2000. However, the rate decreased in 2001 except for Macaranga gigantea dominated stands. These figures were higher than those of regenerated vegetation in degraded land with herbs, shrubs and Imperata cylindrica grassland. On the other hand, annual carbon accumulation of Acacia mangium, eucalyptus pelitta and Gmelia arborea were 5.9-9.9, 7.1-7.2, and 8.3-12.3 t C/ha/yr respectively. Highly degraded vegetations would be the target site for CDM projects. Naturally regenerated forests are not suitable for CDM project because of their high baseline.